European Union law including Brexit in a nutshell - Folsom, Ralph Haughwout (St. Paul, MN : West Academic Publishing, 2017)
"This Nutshell covers the history of the European Union, including BREXIT, its legislative procedures, litigating EU law and the jurisprudence of the European Court of Justice. Free movement of goods, services, people (including mass migration), capital and technology, the EURO in crisis, and extensive internal Union policies are detailed. This Nutshell also reviews EU international trade, foreign investment and business competition (antitrust) law."--
Old Europe -- New Europe, BREXIT -- Law-making in Europe -- Litigating European law -- Free movement -- Internal policies -- External trade and foreign investment law -- Business competition (antitrust) law.
Includes bibliographical references and index.
Keywords: European Union; Law -- European Union countries; Law -- European Union countries; European law; Europe -- European Union countries; Study guides; Study aids; Study guides